Aortic Arch Interruption and Persistent Fifth Aortic Arch in Phace Syndrome: Prenatal Diagnosis and Postnatal Course. Issue 9 (25th March 2015) - Chiappa, Enrico; Greco, Antonella; Fainardi, Valentina; Passantino, Silvia; Serranti, Daniele; Favilli, Silvia
<x xml:space="preserve">Abstract</x> PHACE is a rare congenital neurocutaneous syndrome where posterior fossa malformations, hemangiomas, cerebrovascular anomalies, aortic arch anomalies, cardiac defects, and eye abnormalities are variably associated. We describe the prenatal detection and the postnatal course of a child with PHACE syndrome with a unique type of aortic arch anomaly consisting of proximal interruption of the aortic arch and persistence of the fifth aortic arch. The fifth aortic arch represented in this case a vital systemic‐to‐systemic connection between the ascending aorta and the transverse portion of the aortic arch allowing adequate forward flow through the aortic arch without surgical treatment.